A distinção entre a liberdade ética e a liberdade política em Spinoza - Miranda, Karine Vieira (2024)
The Dutch philosopher Benedictus de Spinoza is dedicated to building a consistent ontological and political philosophy, both of which are distinct, yet intimately connected. The main object of study of this thesis will be his Magnum opus, Ethics Demonstrated According to the Geometric Order (Ethica Ordine Geometrico Demonstrata), accompanied by the Political Treatise (Tractatus Politicus) and the Theological-Political Treatise (Tractatus Theologico- Politicus), as well as other his writings that will be punctuated whenever we consider it appropriate to answer our questions, considerations from his influencers and commentators. The objective of this is to answer, in detail, what is the distinction between ethical freedom and political freedom in Spinoza and what is the necessary confluence between individual power and collective power. To do so, we will need to go through all five parts of Ethics, communicating them with the philosopher's other works, to understand, among other concepts, God (cause of himself and all things, substance, made up of infinite attributes, eternal, unique holder of absolute freedom), the modes (man, body, mind), the genres of knowledge (imagination, reason and intuitive science), the conatus, the affections (primary and secondary), servitude and freedom. Furthermore, we will analyze, among other topics, Spinoza's rupture with finalism and theological tradition, the importance of distancing himself from prejudices, superstition, and ignorance, the relativization of good and bad, and the dictates of reason and remedies for affections. Furthermore, we will briefly return to divine freedom, and human freedom from an ethical perspective, and only then, we will enter into political freedom, distinguishing it from ethics, presenting a reflection on a pedagogical project implicit in Spinoza's philosophy, its role in maintaining freedoms and the double bias of political obedience, especially, considering the most natural of regimes for our philosopher, namely, democracy, where obedience can have a merely secondary role for the subject, in what we will call partial democracy or, even not there will be a place for it, in what we will call total democracy. Therefore, man, Spinoza assures us, as a finite mode, an affection of the absolutely infinite substance, as part of God, can only be partially free: ethically and politically. In the first case, it is about individual freedom, guaranteed by natural law and achieved through the increase of its power [potentia], through adequate knowledge, while in the second, it is about political freedom guaranteed to everyone, both the wise and the wise. to the ignorant, by civil law, from the union of powers.